Making medicines: A case study in innovative academia–industry educational partnerships. Issue 5 (October 2018) - McClain, Elizabeth K.; Johnson-Moton, Yolanda; Larsen, Bryan; Ellis, Rebecca J. Bartlett; Niederhoffer, Eric
The approach to building innovative partnerships between academia and the pharmaceutical industry has expanded to investigate collaborations that offer meaningful outcomes beyond discovery and increased productivity. This case study uses a systems thinking approach to guide the process and analyse the outcome of a partnership undertaken by one pharmaceutical company and academia. The collaborative process established three tiers of evolution over a 3-year period. The outcome was an online module–based course, entitled 'Making Medicines: The Process of Drug Development', that provides information about the drug discovery and development process. Both the course development and the final product serve as a useful case study of how collaboration between academia and industry might be achieved. The development process itself is proposed as an appropriate approach for building educational partnerships.